Warming From Land Use and Land Cover Change Associated With Economic Growth in the Permafrost Regions of the Northern Hemisphere - Xiaoqing Peng; Xuanjia Li; Rong Wang; Oliver W. Frauenfeld; Hengxing Luo; Panpan Wang; Chen Yang; Gubu Qiumo (Earth's Future, 2025)
Abstract Climate warming has resulted in permafrost degradation, leading to land use and land cover changes (LULCC). However, the impacts of LULCC on permafrost and local economies has not been quantified. Here, we analyze air and soil temperatures with gross domestic product per capita as associated with the biogeophysical and biogeochemical effects of LULCC using the CMIP6 experiments and a temperature‐growth rate equation. Air temperature increased by 0.04 K due to biogeophysical processes and 0.23 K from biogeochemical processes, with corresponding soil temperature rises of 0.05 and 0.20 K, respectively. Warming from LULCC is accelerating and could result in economic growth, with a cumulative increase in gross domestic product per capita of $24,000 from biogeophysical effects, and about $470,000 from biogeochemical effects for 1995–2014. Additionally, spatial economic growth patterns indicate increases from south to north, with decreasing economic inequality. These findings could benefit the development or management policies of the future.